STRUCTURAL, VIBRATIONAL, OPTICAL, AND MAGNETIC PROPERTIES OF 0-3 TYPE PARTICULATE PbTiO3-NiFe2O4 COMPOSITES - Pham, Do Chung (Trường Đại học Đà Lạt, 2023)
We synthesized 0-3 type (1-x)PbTiO3-xNiFe2O4 (x = 0.0-0.5) multiferroic composites with two independently crystallized parent phases by the sol-gel method. Structural, surface morphology, vibrational, optical, and magnetic characteristics were investigated by X-ray diffraction (XRD), SEM, Raman scattering, UV-vis absorption, and magnetization (M-H) measurements, respectively. The XRD result showed that the lattice parameter a of the PbTiO3 (PTO) phase decreased while lattice parameter c increased after compositing, leading to a decrease in the tetragonal ratio c/a. SEM images indicated that the NiFe2O4 (NFO) crystals that crystallized later are small and adhere to the surface of the large PTO particles. The strong cohesion between the two components was also revealed by the gradual shift of the Raman peaks to the lower wavelength and the reduction of the Raman intensity as the NFO content increased. The UV-vis absorption result showed the co-absorption spectra of the parent phases in the composites. Magnetization curves presented a sharp increase in saturation magnetization MS with NFO content from 0.014 emu/g for the PTO sample to 14.360 emu/g for the composite containing 50 mol% NFO. This study indicates an effective method in the search for multilayer composites.